Determining of agricultural credit impact on agricultural production value in Turkey - Nermin Bahşi; Eray Çetin (Ciência Rural, 2020)
ABSTRACT: Agriculture is an indispensable activity for all countries. Depending on the increasing population, food needs can be met by increasing agricultural production. In this respect, it is of great importance to investigate the value of agricultural production and the factors affecting agricultural production. This study aimed to examine the impact on the agricultural production value of agricultural bank credit in Turkey. In the study, with the aim of examining the relationship between agricultural credit and agricultural production value in Turkey, 1998-2016 real agricultural loans and agricultural real gross domestic product annual data covering the period given above were used. The statistical analysis tool is ordinary least squares (OLS) techniques. According to OLS regression, the purposed model explains 83.94% of total variance. Regression coefficients show that effect of term is higher than effect of agricultural credits. The reason for this difference may be explained as dependency of credits on macroeconomic indicators and political structure of the country. This study proposes that agricultural credit mechanism in the country needs to be developed to increase the financing opportunities for the realization of technology and modernization investments by farmers.